2016
DOI: 10.1002/oby.21505
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, obesity and the risk of gallbladder and extrahepatic bile duct cancers: A meta‐analysis of observational studies

Abstract: Objective: Epidemiological studies have repeatedly investigated the association between excess body weight and the risk of biliary tract cancer with inconsistent results. The objective of this study was to quantitatively assess the associations between overweight and obesity and the risk of biliary tract cancer. Methods: A comprehensive search of PubMed, Embase, Web of Science, and China National Knowledge Infrastructure databases up to August 2015 was conducted, and the reference lists of retrieved articles f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 71 publications
1
20
0
3
Order By: Relevance
“…Risk factors for gallbladder cancer are mainly related to chronic inflammation, infections or gallbladder pathologies such as gallstones, porcelain gallbladder, gallbladder polyps and biliary cysts . Other risk factors include female sex, advanced age, obesity, postmenopausal hormone replacement and parity …”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for gallbladder cancer are mainly related to chronic inflammation, infections or gallbladder pathologies such as gallstones, porcelain gallbladder, gallbladder polyps and biliary cysts . Other risk factors include female sex, advanced age, obesity, postmenopausal hormone replacement and parity …”
Section: Introductionmentioning
confidence: 99%
“…Obesity contributes to the development of gall stones, and may therefore lead to gallbladder cancer. Li et al [102] showed that overweight people are characterized by a 20% higher gallbladder cancer risk, compared to people with normal weight, whereas for obese people this risk is higher by 60%. Considering gender, women are more prone to this type of cancer than men.…”
Section: Kidney Cancer Wang and Xumentioning
confidence: 99%
“…However, data linking obesity to GBC are conlicting. A recent meta-analysis of 14 prospective cohort and 15 case control studies revealed that excess body weight is indeed a risk factor for GBC development [19].…”
Section: Incidence and Prevalencementioning
confidence: 99%